Contingent valuation and cultural policy design: The case of "Napoli Musei Aperti" - Walter Santagata; Giovanni Signorello (Fondazione Eni Enrico Mattei (FEEM), 1998)
The aim of the paper is twofold: to carry out a contingent valuation study of "Napoli Musei Aperti", a cultural public good provided by the city of Naples, and to explore some alternative schemes of cultural policy. The paper is divided in two parts. In the first one some results from the contingent valuation study are presented. In the second one the use of the contingent valuation as a policy instrument in the public cultural sector is discussed.
Keywords: D60; H41; Q26; Z10; 330; Contingent valuation; Public goods; Cultural goods; Logit spike model; Turnbull estimator; Cultural policy; Willingness to pay; Kulturpolitik; Museum; Theorie; Neapel; Italien